Faith and Social Justice: Implementing the Values of the Kingdom of God in the Context of Poverty in Indonesia - Sidabutar, Mina (Hikmat : Jurnal Agama Kristen, 2024)
Poverty remains a significant social challenge in Indonesia, impacting people's economic well-being, education, and quality of life. In a Christian context, faith is not only spiritual but also calls people to engage in social justice efforts, reflected in the values ​​of the Kingdom of God. This article aims to analyze how the principles of the Kingdom of God can be applied in social service practices to reduce economic disparities and empower the poor. This research uses a descriptive qualitative approach through the study of theological literature, church ministry documents, and reports of community empowerment programs in Indonesia. The results of the study indicate that the active implementation of faith through church-based social services, education, and economic programs can promote justice, empowerment, and social solidarity. In conclusion, Christian faith manifested in concrete actions against poverty not only strengthens individual spirituality but also contributes to the development of a more just and sustainable society.